A theory of banking structure - Das, Sanjiv R.; Nanda, Ashish (Journal of Banking & Finance, 1999)
This paper proposes a theory to analyze the specialization of banking activities based upon the different functions that banks perform when rendering a variety of financial services. The functional difference in the services performed by banks is based upon two dimensions: the degree of information asymmetry involved in providing the service, and the degree of verifiability of the value of the service rendered. This has implications for the length of banking relationships and also determines whether banks develop the right degree of skill specialization and resource intensity for the existing task mix. Costly overspecialization occurs in certain deal type transactions and underspecialization occurs in relationship type transactions. The paper examines how bank-client relationships are structured and proposes an explanation for phenomena such as bank syndication. First-mover advantages and monopoly skills are also shown to be natural outcomes of the model. The analysis has implications for banking regulation, such as for the Glass–Steagall Act, in the sense that it analyzes the effects of this specialization, first enacted within the spirit of the Act.